Designing a conversational agent for supporting data exploration in citizen science - Carolin Stein; Timm Teubner; Stefan Morana (Electronic Markets, 2024)
Data is ubiquitous in today's digitized society. However, access to and literacy in handling data plays a pivotal role in determining who can benefit from it and who can use—or potentially misuse—it. To combat inequalities and address issues such as misinformation, it is essential to enable citizens to effectively access and understand data within their local ecosystems. To address this challenge, we focus on the case of citizen science and propose using a conversational agent to support data exploration and lower barriers to citizen engagement in research projects. Using a design science research approach, we derive design principles and develop a prototypical artifact. Moreover, we conduct an experimental evaluation, demonstrating strong interest among citizens to participate in scientific data analysis and that conversational agents hold great potential in increasing data literacy.
Keywords: O35; O36; I24; 620; Conversational agents; Citizen science; Design science research